The Zambezi delta (Mozambique channel, East Africa): High resolution dating combining bio-orbital and seismic stratigraphy to determine climate (palaeoprecipitation) and tectonic controls on a passive margin - (:unkn) unknown (My University, 2019)
The Zambezi Delta draining the Southern African Plateau and the southern part of the East African Rift is one of a the largest delta of Africa with a long-lasting history starting during Early Cretaceous with more than 12 km of sediments deposited. The Zambezi Delta is therefore a unique archive of the past topographic evolution of southern and eastern Africa and their related deformations, but also of the climate changes, global and regional (consequences of local topographic growths). Understanding this archive supposes to get a high-resolution dating of the sediments. Our two objectives are here (1) to construct an age model of the Zambezi Cenozoic delta using a combination of biostratigraphy, orbital stratigraphy and sequence stratigraphy and (2) to determine the palaeoprecipitation variations of the Zambezi catchment from the Oligocene to present day in a known tectonic framework. The Neogene sequences were dated at high-resolution assuming that the third order sequences are of eustatic origin and record long-term eccentricity cycles. The sequences were correlated in ages on the calculated Earth orbital solutions of Laskar for the time intervals provided by the biostratigraphy (nannofossils, planktonic foraminifers). The palaeoprecipitation record was based on the definition of a humidity index based on pollen analysis and associated botanical associations. The late Oligocene was a quite wet period getting dryer in the uppermost Chattian. The base Tortonian (11 Ma) was a humid period. The Messinian was a dry period with a slight increase of the humidity during the Zanclean and a sharp increase around the Zanclean-Piacenzian boundary. The Zambezi Delta has recorded the uplifts of the Southern African Plateau (around 85 Ma and around 25 Ma) and those of the southward migration of the East African Rift (since 5.5 Ma).
Keywords: African Research